KEMUDAHAN AKSES MARKETPLACE DAN KEPUTUSAN PEMBELIAN GENERASI Z: MEDIASI KEPUASAN PENGGUNA - Wirdayani Wahab (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2026)
This study aims to analyze the effect of marketplace accessibility on Generation Z purchasing decisions by considering the role of user satisfaction. The research employed a quantitative approach using Structural Equation Modeling (SEM) with SmartPLS 4. The population consisted of Generation Z marketplace users. The sampling technique used purposive sampling with a total of 110 respondents determined based on the number of research indicators. The variables examined included marketplace accessibility, user satisfaction, and Generation Z purchasing decisions. The results revealed that marketplace accessibility has a positive and significant effect on Generation Z purchasing decisions. This indicates that ease of navigation, product searching, price comparison, and transaction processes can enhance consumer purchasing decisions. Meanwhile, user satisfaction did not significantly influence purchasing decisions. In addition, user satisfaction was unable to moderate the relationship between marketplace accessibility and purchasing decisions. This study implies that marketplace providers need to improve system usability aspects to attract Generation Z consumers. These findings strengthen the Technology Acceptance Model, which emphasizes perceived ease of use as an important factor influencing digital consumer behavior.